Differential blood pressure effects of ibuprofen, naproxen, and celecoxib in patients with arthritis: the PRECISION-ABPM (Prospective Randomized Evaluation of Celecoxib Integrated Safety Versus Ibuprofen or Naproxen Ambulatory Blood Pressure Measurement) Trial. (28th August 2017) - Ruschitzka, Frank; Borer, Jeffrey S; Krum, Henry; Flammer, Andreas J; Yeomans, Neville D; Libby, Peter; Lüscher, Thomas F; Solomon, Daniel H; Husni, M Elaine; Graham, David Y; Davey, Deborah A; Wisniewski, Lisa M; et al.
Abstract : Aims: Non-steroidal anti-inflammatory drugs (NSAIDs), both non-selective and selective cyclooxygenase-2 (COX-2) inhibitors, are among the most widely prescribed drugs worldwide, but associate with increased blood pressure (BP) and adverse cardiovascular (CV) events. PRECISION-ABPM, a substudy of PRECISION was conducted at 60 sites, to determine BP effects of the selective COX-2 inhibitor celecoxib vs. the non-selective NSAIDs naproxen and ibuprofen. Methods and results: In this double-blind, randomized, multicentre non-inferiority CV-safety trial, 444 patients (mean age 62 ± 10 years, 54% female) with osteoarthritis (92%) or rheumatoid arthritis (8%) and evidence of or at increased risk for coronary artery disease received celecoxib (100–200 mg bid), ibuprofen (600–800 mg tid), or naproxen (375–500 mg bid) with matching placebos in a 1: 1: 1 allocation, to assess the effect on 24-h ambulatory BP after 4 months. The change in mean 24-h systolic BP (SBP) in celecoxib, ibuprofen and naproxen-treated patients was -0.3 mmHg [95% confidence interval (CI), −2.25, 1.74], 3.7 (95% CI, 1.72, 5.58) and 1.6 mmHg (95% CI, −0.40, 3.57), respectively. These changes resulted in a difference of − 3.9 mmHg ( P  = 0.0009) between celecoxib and ibuprofen, of − 1.8 mmHg ( P  = 0.12) between celecoxib and naproxen, and of − 2.1 mmHg ( P  = 0.08) between naproxen and ibuprofen. The percentage of patients with normal baseline BP who developed hypertension (mean 24-h SBP ≥ 130 and/or diastolic BP ≥ 80 mmHg) was 23.2% for ibuprofen, 19.0% for naproxen, and 10.3% for celecoxib (odds ratio 0.39, P  = 0.004 and odds ratio 0.49, P  = 0.03 vs. ibuprofen and naproxen, respectively). Conclusions: In PRECISION-ABPM, allocation to the non-selective NSAID ibuprofen, compared with the COX-2 selective inhibitor celecoxib was associated with a significant increase of SBP, and a higher incidence of new-onset hypertension. ClinicalTrials: gov number NCT00346216